From Breakup of Nuna to Assembly of Rodinia: A Link Between the Chinese Central Tianshan Block and Fennoscandia - Huang, Zongying; Yuan, Chao; Long, Xiaoping; Zhang, Yunying; Du, Long (Tectonics, 2019)
The transition from breakup of Nuna (or Columbia, 2.0-1.6 Ga) to assembly of Rodinia (1.0-0.9 Ga) is investigated by means of U-Pb and Lu-Hf data of detrital zircons from three Neoproterozoic metasedimentary rocks in the Central Tianshan Block (CTB), NW China. These data yield six age peaks around 1.0, 1.13, 1.34, 1.4-1.6, 1.75, and 2.6 Ga. Few zircons are detected between 2.0 and 2.5 Ga. The Paleoproterozoic to Neoproterozoic detrital zircons have Hf isotopic compositions (-22.1 to +13.0) similar to those of coeval magmatic rocks in the CTB, indicating a proximal provenance. These results, together with the geological evidence and the presence of 1.4 Ga orogenic granitoids in the CTB, rule out most cratons as the CTB sources but support a Fennoscandia ancestry. Zircon U-Pb ages and Hf isotopic compositions from the CTB and Fennoscandia suggest that from 1.8 to 1.4 Ga, the epsilon(Hf)(t) values increased toward more positive values, consistent with an exterior orogen characteristic that the lower crust was replaced by a juvenile arc crust. In contrast, from 1.4 to 0.9 Ga, zircon epsilon(Hf)(t) values decreased to more negative values, reflecting an interior orogen, characterized by enhanced contribution of recycled crustal material from collided continental fragments. This marked shift most likely reflected a transition from breakup of Nuna to assembly of Rodinia, accomplished by a transformation from an exterior orogen to an interior one.